A Rapid Method for the Determination of Delta Amino-laevulinic Acid in Urine - Mehani, Shawkia (Br J Ind Med, 1964)
A rapid colorimetric method, sensitive to 0·5 μg., is described for the determination of delta amino-laevulinic acid in urine. The method consists of a modification of the picrate methods of Shuster in which interference by porphobilinogen is avoided by the use of an ion exchange resin. The method is found to give results which compare in accuracy with the longer standard method of Mauzerall and Granick.